2019
DOI: 10.3390/cells8050464
|View full text |Cite
|
Sign up to set email alerts
|

Leucocyte Telomere Length and Glucose Tolerance Status in Mixed-Ancestry South Africans

Abstract: Telomeres are DNA-tandem repeats situated at the ends of chromosomes and are responsible for genome stabilization. They are eroded by increased cell division, age and oxidative stress with shortened leucocyte telomeres (LTL) being associated with inflammatory disorders, including Type II diabetes. We assessed LTL in 205 participants across glucose tolerance groups at baseline and after three years in the mixed ancestry population of South Africa which have been shown to have high rates of obesity and T2DM. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
5
1
Order By: Relevance
“…Compared with our results, a recent study in 205 individuals in South Africa noted a significant negative correlation between leukocyte telomere length and GGT (r = − 0.16, p = 0.03) 34 . In contrast to our findings, no associations between telomere length and indicators of oxidative stress including GGT were observed in a study in 143 elderly Dutch men and 109 Greek elderly men 33 .…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Compared with our results, a recent study in 205 individuals in South Africa noted a significant negative correlation between leukocyte telomere length and GGT (r = − 0.16, p = 0.03) 34 . In contrast to our findings, no associations between telomere length and indicators of oxidative stress including GGT were observed in a study in 143 elderly Dutch men and 109 Greek elderly men 33 .…”
Section: Discussioncontrasting
confidence: 87%
“…As telomere length, GGT is also strongly associated with risk of cardiovascular disease 28 , metabolic syndrome 29 , 30 , and mortality 31 , 32 . Although the association between GGT and telomere length is barely studied 33 , 34 . Advanced understanding of their interrelation already in young adulthood may be relevant to provide new insights on the underlying pathways of disease development.…”
Section: Introductionmentioning
confidence: 99%
“…The first study investigated participants from the multiethnic Women's Health Initiative and reported only limited clinical usability of RTL for diabetes risk stratification among postmenopausal women 40 . The second study analyzed RTL and glucose tolerance status in 205 mixed-ancestry South Africans and found no association of RTL with glycaemia 41 .…”
Section: Discussionmentioning
confidence: 99%
“…It occurs after the age of 40. It accounts for 90-95% of all diabetes cases, although unfortunately it is also more common in young people, especially in developed countries (Weale et al, 2019). Sokolov (2012) explains that in this type of diabetes, the pancreas produces insulin, but in small amounts, or the body has developed a resistance to it.…”
Section: Introductionmentioning
confidence: 99%